In-vitro protocol for mass multiplication in bougainvillea (Bougainvillea sp) cv. Mahatma Gandhi and Refulgens - KUMARI, PRATIKSHA; SWAROOP, KISHAN; JANAKIRAM, T; SINGH, S K; PRASAD, K V; JAIN, RITU (The Indian Journal of Agricultural Sciences, 2016)
Bougainvillea (Bougainvillea sp) is recognized as a high value landscape plant. It is usually propagated by hardwood cuttings, but in certain varieties, rooting per cent is very low, ultimately the rate of multiplication is less. Therefore, the present investigation was carried with an objective to standardize the protocol for quick, easy and mass multiplication of two difficult-to-root cultivars Mahatma Gandhi and Refulgens, using in vitro techniques. Nodal sections with axillary buds were excised, surface-sterilized and cultured on MS medium supplemented with plant growth regulators. Pre-treatment agitation of explants in carbendazim (0.1%) + Metalaxyl (0.1%) + 8-HQC (200 mg/l) for 3 hr followed by quick dip in ethyl alcohol (70%; v/v) for 30 sec and surface sterilization in HgCl2 (0.1%) for 5 min was used for reducing contamination. MS medium with BAP (5 mg/l) was found to be the best with highest percentage of culture establishment (81.13) and the fastest bud sprout (8.18 days). MS medium supplemented with BAP (4.0 mg/l) and kinetin (0.5 mg/l) resulted in highest shoot proliferation in both the cultivars. The best treatment for micro-shoot elongation was the one where MS medium was supplemented with 0.5 mg/l GA3 giving the highest elongation (3.89 cm). In vitro rooting of micro-shoots was done in half-strength MS medium supplemented with 1.0 mg/l IBA. Hardening was done in glass jar with polypropylene cap.